2014
DOI: 10.1177/0961203314546017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of creatine supplementation in childhood-onset systemic lupus erythematosus: a randomized, double-blind, placebo-controlled, crossover trial

Abstract: Clinicaltrials.gov number: NCT01217320.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
0
26
0
2
Order By: Relevance
“…This notion also appears to hold true regarding bone metabolism. Despite some conflicting results (12,13), clinical trials have demonstrated a beneficial effect of creatine supplementation in conjunction with resistance training on bone mass (9)(10)(11). For instance, it was recently demonstrated that one year of creatine supplementation at a daily dose of 0.1 g/kg bw (~ 7 g) associated with a resistance training program preserved femoral neck BMD and increased femoral shaft superiosteal width in older women (10).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This notion also appears to hold true regarding bone metabolism. Despite some conflicting results (12,13), clinical trials have demonstrated a beneficial effect of creatine supplementation in conjunction with resistance training on bone mass (9)(10)(11). For instance, it was recently demonstrated that one year of creatine supplementation at a daily dose of 0.1 g/kg bw (~ 7 g) associated with a resistance training program preserved femoral neck BMD and increased femoral shaft superiosteal width in older women (10).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some (9)(10)(11), but not all (12,13), clinical studies have demonstrated a positive effect of creatine supplementation on bone health, particularly in patients with myopathies and in elderly individuals (10,11). In this regard, it was recently demonstrated that 12 months of creatine supplementation combined with resistance training attenuated femoral neck BMD loss to a greater extent than resistance training alone in postmenopausal women (10).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…As above reported, creatine is normally converted into creatinine, thus serum concentration of the latter may increase during creatine supplementation despite a normal and stable renal function. In cases where precise evaluation of renal function during creatine supplementation is critical, (51)Cr‐EDTA renal clearance is probably more reliable than creatinine concentration or clearance …”
Section: Discussionmentioning
confidence: 99%
“…Because the conversion of creatine to creatinine is determined by a chemical balance with a fixed time constant, an increase of total creatine content will automatically result in increased production of creatinine, leading to elevated levels of serum and urine creatinine. Thus, as previously discussed (see the paper by Hayashi et al, reported above in the section “Creatine administration at a dose lower than 10 g/d”), serum concentration of creatinine is very difficult to interpret in these patients (among others, this concept was reiterated by Yoshizumi and Tsourounis). Later research, however, denied that creatinine increases after creatine administration …”
Section: Need For High‐dose Creatine Administration and Its Safetymentioning
confidence: 97%
See 1 more Smart Citation